Water Conflicts in Guanacaste, Costa Rica: Responses to Tourism Development - Cañada, Ernest (2019)
In this article, we aim to examine whether socio-ecological conflicts linked to dispossession processes by residential tourism investments can be analyzed from the viewpoint that builds these sector’s relationship with tourism. We analyze the specific case of Guanacaste, Costa Rica, where there has been high intensity both in the development of tourism investment and in ecological conflicts over water between rural communities and investments in residential tourism supported by the State. The question we ask ourselves is whether a discourse of rejection of tourism forms in a rural context of these characteristics, as has happened in certain urban destinations, or rather, in the framework of intense conflicts and negotiations, the arguments of the community social movements that react to these mechanisms of dispossession relate to the demands of an inclusive tourism.